Pengembangan Media Edukasi Gizi Game NutriMaze-Man tentang Tumpeng Gizi Seimbang pada Siswa SMP Negeri 1 Sumbul - Mariana Rebecca Sirait; Hardi Firmansyah; Esi Emilia; Caca Pratiwi; Erni Rukmana (Jurnal Sains Boga, 2026)
The low level of students' knowledge regarding Balanced Nutritional Tumpeng and the limited availability of nutrition education media have the potential to influence inappropriate food choices and increase the risk of nutritional problems. Therefore, it is necessary to develop innovative and interactive nutrition education media to improve students' understanding of Balanced Nutritional Tumpeng. This study aims to: 1) develop a game-based nutrition education media NutriMaze–Man to measure the increase in students' knowledge of Balanced Nutritional Tumpeng at SMP Negeri 1 Sumbul through a comparison of pretest and posttest scores; and (2) determine the feasibility of the NutriMaze–Man game media as a nutrition education media for students at SMP Negeri 1 Sumbul. This type of research is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The study was conducted at SMP Negeri 1 Sumbul in September–November 2025 with a target of 35 students in grades VIII–3. Data analysis used a feasibility test and an N-Gain test. The results showed that the NutriMaze–Man nutrition game media was considered appropriate with an average score of 76.5% from material experts and 96% from media experts. Student responses were categorized as excellent with 91.1% in the small group test and 86.9% in the large group test. The N-Gain test showed an average increase in posttest scores of 11.72 with an N-Gain value of 28%, which is categorized as ineffective.